2022
DOI: 10.3390/scipharm90030043
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Release Two-In-One Clonazepam Matrix Lozenge Tablets for Managing Anxiety-Related Disorders: Formulation, Optimization and In Vivo Evaluation

Abstract: Clonazepam (CLZ), an antipsychotic drug reported for its efficiency in managing anxiety-related disorders, is being marketed only as conventional tablets. Some patients have abstention to swallow the conventional tablets; therefore, the proposed study was aimed at developing a buccal lozenge tablet by direct compression of two types of optimized granules. Conazepam’s water solubility was first enhanced by a solid dispersion technique for a fast and better dissolution of type 1 granules, while the impact of gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The in vitro disintegration was higher than 25% within 3 min, 37% within 5 min, and 61% within 15 min, and complete disintegration occurred within 30 min. All the data indicated that the manufactured lozenges could be effectively used in drug delivery, and similar outcomes were reported in the literature [67].…”
Section: Characterization Of Lozengessupporting
confidence: 81%
“…The in vitro disintegration was higher than 25% within 3 min, 37% within 5 min, and 61% within 15 min, and complete disintegration occurred within 30 min. All the data indicated that the manufactured lozenges could be effectively used in drug delivery, and similar outcomes were reported in the literature [67].…”
Section: Characterization Of Lozengessupporting
confidence: 81%
“…A zero-order profile was not possible to be traced for this formulation. Focusing on the Korsmeyer-Peppas model, frequently used for determining the release kinetics of polymeric dosage forms, the value of the parameter c2 holds particular relevance in characterizing the drug transport mechanism (Gomaa et al, 2022). Accordingly, c2 values close to 0.5 are indicative of a Fickian diffusion process, whereas values ranging from 0.5 to 1.0 suggest an anomalous (non-Fickian) transport.…”
Section: Thermodynamic and Structural Characterization Of Asdsmentioning
confidence: 99%